An exploration of information exchange by adolescents and parents participating in adolescent idiopathic scoliosis online support groups. Issue 1 (December 2016) - Schwieger, Traci; Campo, Shelly; Steuber, Keli; Weinstein, Stuart; Ashida, Sato
Abstract Background Research indicates that healthcare providers frequently fail to adequately address patients' health information needs. Therefore, it is not surprising that patients or parents of a sick child are seeking health information on the internet, in particular in online support groups (OSGs). In order to improve our understanding of the unmet health information needs of families dealing with adolescent idiopathic scoliosis (AIS), this study assessed and compared the types of information that adolescents and parents are seeking in OSGs. Methods This study used two publicly accessible AIS-related OSGs on the National Scoliosis Foundation (NSF) website that targeted those who are receiving brace treatment and those under observation without treatment. Information exchanges were coded as providing or seeking information. Types of information being exchanged were categorized into several AIS-specific and brace-specific categories. Through a review of over 8, 000 messages, 305 adolescents with AIS and 300 parents of a child with AIS were identified and categorized based on stage of illness/treatment. One message from each individual was randomly selected and coded for analysis. Results There were significantly more (p  < 0.001) parents that had a recently diagnosed child compared to recently diagnosed adolescents participating in the AIS-related OSGs, whereas there were significantly more (p  = 0.004) adolescents that experienced brace treatment compared to parents of a child that experienced brace treatment. The most frequent information exchanged by adolescents and parents was AIS-related concerns regarding causes, diagnosis, and progression of the condition. However, compared to adolescents, parents exchanged this AIS-related information significantly more (p  < .001) in their posts. Finally, compared to parents, adolescents exchanged significantly more information about appearance-related concerns regarding both AIS-related deformity (p  < 0.002) and wearing a brace (p  < 0.001). Conclusion Families dealing with AIS are participating in OSGs to exchange information, in particular information related to the condition and to treatment. This study found similarities and differences regarding how information was exchanged (providing or seeking) and regarding frequency and types of information exchanged. Knowledge of these similarities and differences may be useful for improving health communication in the healthcare setting, at home, and for development and improvement of AIS-related website support.